The Influence of Five Rootstocks on the Fruit Quality of Three Orange Cultivars - AHMED, HUSAIN S.; AL-SHURAFA, MOHAMED Y.; SHALADAN, MOHAMED S. (The Libyan Journal of Agriculture, 2023)
The physical and chemical fruit qualities of 3 orange cultivars (Hamlin. Washington Navel, and Valencia) grown on 5 different rootstocks (Sour Orange. Cleopatra Mandarin. Rough Lemon. Troyer Citrange and Rangpur Lime) were determined over 2 growing seasons (1977 and 1978). Orange fruits from trees grown on Rough Lemon rootstock were large in weight and volume, but relatively low in TSS. acidity, and ascorbic acid. Fruits from trees grown on Sour Orange and Cleopatra Mandarin, had similar fruit characters, they were relatively small in size and weight but contained high amounts of TSS. acidity, and ascorbic acid. Troyer Citrange and Rangpur Lime took intermediate trend, and were usually inconsistent in their effect on the orange fruit quality.